Perspectives on free and open source software. - Feller, Joseph, ....-; Fitzgerald, Brian, 1959-; Hissam, Scott A., ....- (Cambridge : MIT, 2005)
What is the status of the Free and Open Source Software (F/OSS) revolution? Has the creation of software that can be freely used, modified, and redistributed transformed industry and society, as some predicted, or is this transformation still a work in progress? "Perspectives on Free and Open Source Software brings together leading analysts and researchers to address this question, examining specific aspects of F/OSS in a way that is both scientifically rigorous and highly relevant to real-life managerial and technical concerns.The book analyzes a number of key topics: the motivation behind F/OSS -- why highly skilled software developers devote large amounts of time to the creation of "free" products and services; the objective, empirically grounded evaluation of software -- necessary to counter what one chapter author calls the "steamroller" of F/OSS hype; the software engineering processes and tools used in specific projects, including Apache, GNOME, and Mozilla; the economic and business models that reflect the changing relationships between users and firms, technical communities and firms, and between competitors; and legal, cultural, and social issues, including one contribution that suggests parallels between "open code" and "open society" and another that points to the need for understanding the movement's social causes and consequences.